2007
DOI: 10.1097/ta.0b013e31804d490b
|View full text |Cite
|
Sign up to set email alerts
|

Prone Ventilation in Trauma or Surgical Patients With Acute Lung Injury and Adult Respiratory Distress Syndrome: is it Beneficial?

Abstract: ALI/ARDS patients who received prone kinetic therapy had greater improvement in PaO2/FiO2 ratio, lower mortality, and less pulmonary-related mortality than did supine positioned patients. The use of a prone-oscillating bed appears advantageous for trauma and surgical patients with ALI/ARDS and a prospective, randomized trial is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…One treatment concept adopted from results in critically ill patients to prevent acute LI (ALI) and ARDS 21 and postulated to be beneficial in mechanically ventilated patients with thoracic trauma is prophylactic kinetic positioning. 7,22 However, considering the risk of ventilator-associated pneumonia and economic aspects, we have to clearly identify patients who benefit from this treatment, which is mainly based on the MSCT findings obtained within a certain range after trauma. Hence, the identification of a valid biomarker to support the primary diagnosis and enable a subsequent follow-up of the lung epithelial barrier integrity would have immediate impact on treatment strategies supporting the conclusion of McAuley and Matthay, 16 who pointed out that a diagnostic biomarker such as CC16 might allow an optimum ventilatory strategy to be tailored to the needs of an individual patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One treatment concept adopted from results in critically ill patients to prevent acute LI (ALI) and ARDS 21 and postulated to be beneficial in mechanically ventilated patients with thoracic trauma is prophylactic kinetic positioning. 7,22 However, considering the risk of ventilator-associated pneumonia and economic aspects, we have to clearly identify patients who benefit from this treatment, which is mainly based on the MSCT findings obtained within a certain range after trauma. Hence, the identification of a valid biomarker to support the primary diagnosis and enable a subsequent follow-up of the lung epithelial barrier integrity would have immediate impact on treatment strategies supporting the conclusion of McAuley and Matthay, 16 who pointed out that a diagnostic biomarker such as CC16 might allow an optimum ventilatory strategy to be tailored to the needs of an individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent investigations have shown that thoracic trauma is associated with altered posttraumatic inflammation, impaired outcome, and increased rates of pneumonia and Acute Respiratory Distress Syndrome (ARDS) in these critically ill patients. 4 -6 Because the clinical course of patients with multiple injuries and lung injury (LI) can be influenced by prophylactic positive end-expiratory pressure ventilation or kinetic positioning in the intensive care unit (ICU), 7,8 determination of the extent of thoracic injury/lung damage is warranted. According to Advanced Trauma Life Support 9 criteria, diagnosis of thoracic damage is usually performed via initial chest roentgenogram followed by multislice computed tomography (MSCT) early after traumatic impact.…”
mentioning
confidence: 99%
“…Historically, "rescue" therapies earned this name because they were used as a last resort effort to improve oxygenation in life-threatening situations. (3,4,11,14,15,17,18,22,25,26) Future prospective studies should continue to investigate whether or not routine initiation of a rescue therapy in patients who have severe ARDS prior to the development of life-threatening critical hypoxemia would improve survival to hospital discharge. …”
Section: Resultsmentioning
confidence: 99%
“…9 Although no significant differences in mortality were demonstrated at the end of the 10-day study period, at the time of ICU discharge, or at 6 months, the researchers did find that the use of the prone position improved oxygenation in more than 70% of the instances in which it was used. 11 Prone positioning also improves postural drainage, so that more secretions can be suctioned from the patient, improving ventilation. 10 A study of 61 patients with acute lung injury and ARDS (44 patients were positioned supine, 13 placed prone, and 4 patients who were initially placed supine were changed to prone positioning) found that prone kinetic therapy (use of a bed that turns continuously and slowly more than 40 degrees along its longitudinal axis) resulted in greater improvement in PaO 2 /F i O 2 ratios, reduced pulmonary-related mortality, fewer ventilator days, and shorter hospital length of stay than supine kinetic therapy.…”
Section: Does Prone Positioning Work?mentioning
confidence: 99%
“…11 My facility administers bolus enteral feedings while the patient is supine. Patients should be adequately sedated while in the prone position, and may need more sedation than what was administered when the patient was in a supine position.…”
Section: Your Rolementioning
confidence: 99%